Islamic wood work motifs of Iran and India in Mughal era / Mahshid Kakouei Ezbarami - Mahshid, Kakouei Ezbarami (2016)
This survey was conducted to identify the design of motifs and pattern found in the wooden objects of Iran and India during the Mughal period. The art of the Timurid period in Iran is best known in scholarly literature for its unsurpassed achievements in the field of miniature painting, and, to a lesser extent, for its architecture. The decorative art of this period, such as wooden work, have been largely neglected, in part because the amount of preserved material was thought to be limited. This misconception has been fostered by the fact that few of the numerous examples held in public collections have been published; while many of those objects that have been published are misattributed. A similar situation exists with regard to the general study of Iranian and Indian wooden work, in that published material is limited in comparison to the great number of extant objects, while many questions of attribution and dating have yet to be successfully resolved. In so far as the wooden work of the Mughal period is concerned, some progress has been made in terms of the establishment of data and provenance for a limited number of objects, however, the majority of these remain to be identified, studies and further classified. It is therefore essential to establish a means by which to identify Mughal wooden work. This is one of the intentions of the present dissertation. The current study related to motifs, as effective elements in the review and analysis of artistic works, possesses an important place in the field. To obtain the best results about the roots of the motifs used in Iranian and Indian wooden objects, after clarification of the characteristics of Islamic art, the art of objects and motifs in Islamic lands has been perused in the context of the form of the motifs in various eras. To access this intention some leading and typical works from each era have been chosen and shown. After a review of the motifs, a complete technical and artistic description of the objects is provided that describes the decorative structure of the ornamental themes. In addition, the scientific, artistic terminology for the ornamental themes is provided. Thus, the researcher has brought to light a new academic approach to the study of Islamic wooden art by analysing the motifs of the samples gathered from Iran and India using the visual semiotic and Iconography theories. In this survey, the researcher utilized the qualitative technique in order to produce the best data. Analysis was conducted and the researcher referred to the selected motifs to produce a continuum of original motif that has been studied previously. Each motif has been studied and refers to the elements of the art and design in each study conducted. After analysis of the motifs, the meaning of the abstract and natural motifs used in the decoration of wooden objects was identified. The results showed the role of religion, the artists and the meaning of the motifs in transferring the pattern from Iran to India.